Cluster analysis of the acute diarrhea causes in young children admitted to the infectious diseases unit - O. H. Ivanko; V. M. Bondarenko (Zaporozhye State Medical University, 2021)
Aim. To use the cluster analysis of clinical and laboratory data, characteristic to children aged 6 to 24 months with acute diarrhea, in demonstrating the signs of infectious or functional intestinal disorders. Materials and methods. 56 children admitted to the children's infectious unit with diarrhea and 31 healthy toddlers of the control group were observed. Anamnesis, laboratory blood and urine tests, microscopy and bacteriological cultures of feces on selective media and tests to identify adeno- and rotaviruses were performed. The presence of Clostridium difficile A/B toxins in the stool, hemoglobin, fecal calprotectin (FC) and the content of undigested fecal carbohydrates also were studied. Results. Children who in their majority have received antibiotics only in 58.9 % of cases were corresponding to the bacterial or viral nature of the disease or the infection was clinically highly probable. Another 41.1 % of patients has experienced non-infectious diarrhea. In 7.1 % of all cases the diarrhea was triggered by an increase of the carbohydrate content in the stool. Diarrhea had the same mechanism in 3.4 % of patients with Giardia lamblia. In 17.9 % of patients the frequent bowel movements were the manifestation of symptomatic (parenteral) diarrhea caused by extraintestinal diseases, and in another 7.1 % the intestinal hypermotility was not explained but resembled irritable bowel syndrome in adults. Additionally, cluster analysis identified 5.4 % of patients with non-infectious diarrhea who had only significantly increased FC corresponding to allergic or immune inflammation in the gut. Conclusions. The classification of patients for the causes of diarrhea became possible due to the microbiological tests and highly informative markers of intestinal health - fecal calprotectin and reducing substances (carbohydrates) in the stool.